2013
DOI: 10.4081/aiua.2013.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic direct rectal injury: An unusual complication during suprapubic cystostomy (SPC) insertion and its laparoscopic management

Abstract: Suprapubic cystostomy (SPC) is commonly used, instead of indwelling urethral catheter- ization, as indicated in many pathological conditions. Although considered to be a safe procedure that can be easily performed in an outpatient basis several complications have been reported in international literature. Bowel injury can be a serious complication with the small intestine affected in the majority of cases. We present a case of an acci- dental rectal injury by a suprapubic catheter misplacement, in a 76 year ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Emerging evidence has shown that there are many common and different complications during suprapubic cystostomy insertion, such as rectal injury, bowel perforation (Ahmed, Mehta, & Rimington, ; Rajmohan, Aguilar‐Davidov, Tokas, Rassweiler, & Gozen, ; Witham & Martindale, ; Wu, Su, & Lin, ). However, there is still evidence reporting some rare complications during the catheter change, such as bowel injury, small bowel perforation and malpositioning in urethra (Kass‐Iliyya et al., ; Mongiu et al., ; Vaidyanathan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that there are many common and different complications during suprapubic cystostomy insertion, such as rectal injury, bowel perforation (Ahmed, Mehta, & Rimington, ; Rajmohan, Aguilar‐Davidov, Tokas, Rassweiler, & Gozen, ; Witham & Martindale, ; Wu, Su, & Lin, ). However, there is still evidence reporting some rare complications during the catheter change, such as bowel injury, small bowel perforation and malpositioning in urethra (Kass‐Iliyya et al., ; Mongiu et al., ; Vaidyanathan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, risk of complications may increase with incorrect performance of the technique or with poor training and education 8. The incidence of bowel perforation or other injury is reported to be as high as 2.7%, and iatrogenic direct rectal injury has also been reported 9.…”
Section: Introductionmentioning
confidence: 99%
“…1 There have been several reports of injuries to the ileum and sigmoid colon and a few reports of injuries to the stomach and rectum. [2][3][4] Stomach injury can occur in the form of iatrogenic suprapubic gastrostomy. 4 We did not find report of jejunal injury in the literature.…”
Section: Introductionmentioning
confidence: 99%